Towards wide-scale adoption of open science practices: The role of open science communities. (3rd July 2021) - Armeni, Kristijan; Brinkman, Loek; Carlsson, Rickard; Eerland, Anita; Fijten, Rianne; Fondberg, Robin; Heininga, Vera E; Heunis, Stephan; Koh, Wei Qi; Masselink, Maurits; Moran, Niall; Baoill, Andrew Ó; et al.
Abstract: Despite the increasing availability of Open Science (OS) infrastructure and the rise in policies to change behaviour, OS practices are not yet the norm. While pioneering researchers are developing OS practices, the majority sticks to status quo . To transition to common practice, we must engage a critical proportion of the academic community. In this transition, OS Communities (OSCs) play a key role. OSCs are bottom-up learning groups of scholars that discuss OS within and across disciplines. They make OS knowledge more accessible and facilitate communication among scholars and policymakers. Over the past two years, eleven OSCs were founded at several Dutch university cities. In other countries, similar OSCs are starting up. In this article, we discuss the pivotal role OSCs play in the large-scale transition to OS. We emphasize that, despite the grassroot character of OSCs, support from universities is critical for OSCs to be viable, effective, and sustainable.